The Effect of Papaya (Carica papaya L.) Leaf Extract to the Number of Trypanosoma evansi Steel in Liver and Kidney of Mice (Mus musculus L. 1758) - Yahya, Yudi; Nurliani, Anni; Santoso, Heri Budi (KnE Life Sciences, 2017)
The purpose of this study proved the activity of the ethanolic extract of papaya leaf as anti-trypanosomiasis agent, determined the dose of extract which having an effect in inhibiting growth of T. evansi, and evaluated the histopathology of liver and kidney infected by Trypanosoma evansi Steel. Male Balb-c mice were infected by 3 × 107 T. evansi isolates. The native method was used to determine the level of parasitemia.The preparation was made using cytological smear method and paraffin method. The results showed that ethanolic extract of papaya leaf decreased the number of T. evansi. Ethanolic extract of papaya leaf at a dose of 300 mg · kg–1 BW is the most influential dose to reduce the number of T. evansi in liver and kidney of mice. Liver reveals degenerative change varying such as congestion, lipid degeneration, vacuolar degeneration, necrosis, and cellular infiltration. Kidney reveals tubular degeneration, necrosis, cellular infiltration, and glomerulonephritis. Keywords: Carica papaya L.; kidney; liver; mice; Trypanosoma evansi Steel